On the TC/MAX criterion for code acquisition and its application to UWB systems - WANG Jiang; BI Guang-guo; ZHANG Zai-chen (Tongxin xuebao)
Due to the difficulty of threshold setting in code acquisition,a new hybrid criterion called TC/MAX （threshold crossing/maximum selection） was presented for code acquisition.To test the proposed criterion,the general formulation was applied to the particular case of ultra wide bandwidth （UWB） communication systems.Analysis and simulation show that the proposed scheme can improve the probability of detection significantly,compared with TC criterion.